Digest of the laws of the Fifty Seventh Congress from 1901 - 1903 - Cole, Amy (My University, 1907)
Introduction: Material from Statutes of United States of America. First and second sessions 1901 - 1903. Passed at the first session, which was begun and held at the City of Washington in the District of Columbia, on Monday, the 2n’d day of December 1901 being the "first Monday in December", and was adjourned without day on Tuesday, the first day of July nineteen hundred and two, the long session closing on the even years. There was no Vice President at the begining of the session, owing to the fact that Vice President Roosevelt took the presidential chair after the assassination of President Mc Kinlev, William P. Frye acted as President of the Senate pro-tempore on the twenty second day of May nineteen hundred and two, Orville H. Platt was chosen acting President protempore; David B. Henderson Speaker of the House of Representative.
Citation: Cole, Amy. Digest of the laws of the Fifty Seventh Congress from 1901 - 1903. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Congress; Fifty Seventh Congress; Turn-of-the-Century; Laws; Legislation; Legislative Branch; Theses